Anatomia óssea, muscular e considerações adaptativas do membro torácico de Tapirus Terrestris (Perissodactyla, Tapiridae) - Pereira, Saulo Gonçalves (2013)
CHAPTER II: Tapirus terrestris (Linneaus, 1758) is a mammal found in South America and in almost all Brazilian biomes. The aim of this study was to describe the anatomy of bone and muscle of the scapular cingulum and arm of Tapirus terrestris and compare it with other species of mammals, especially equines. We used four animals donated to the Laboratory of Education and Research of Wild Animals of the Federal University of Uberlândia, after their death with no trauma. The bones were carefully analyzed, described and the muscles were dissected, analyzed and described in accordance with the usual techniques of gross anatomy. The skeleton of the scapular cingulum and arm of Tapirus terrestris is formed by scapula and humerus bones, the lateral muscles of the scapula are subclavian m., deltoid m. supraspinatus m. and infraspinatus, teres minor m., subscapularis m., teres major m., coracobrachialis m., shoulder joint m., biceps brachii m., brachial m. triceps, forearm tensor fasciae m., anconeus m. The muscular and bone standard found is similar to the horse (Equus caballus) and to other wild and domestic animals, as raccoon, ruminants, deer, among others. CHAPTER III: Currently the Brazilian tapir is the only native representative of the order Perissodactyla in Brazil, and is also the largest land mammal. T. terrestris belongs to the order of Perissodactyla as horses too. This study aimed to describe the bone and muscular anatomy of the forearm and hand in Tapirus terrestris and also compare with other mammalian species. We used five anatomical specimens donated from a breeder to the Laboratory for Teaching and Research on Wild Animals of the Federal University of Uberlândia after death with no trauma. The bones were analyzed, the muscles dissected, and both described. The bones forming the skeleton of the forearm and hand of tapir are the ulna, radius, metacarpals, carpals, phalanges and sesamoid. The muscles are extensor carpi radialis m., ulnar side m., flexor carpi radialis m., extensor radialis common m., extensor digitorum longus II, III, IV and V, lateral digital extensor m., long abductor m., superficial digital flexor m., digital flexor m., flexor carpi ulnaris m., flexor carpal oblique m., and interosseous m. and lumbricals m. CHAPTER IV: Tapirus terrestris is one of the largest mammals of the Americas, it is distributed from south of Brazil and Argentina, to the north of the South American continent. This study aimed to trace a brief history of the Tapirus animals emergence using a literature review and presents environmental and morphological adaptations of the cingular scapular bones of the arm, forearm and hand of T. terrestris. We used four Tapirs skeletons donated to the Laboratory of Education and Research on Wild Animals of the Federal University of Uberlândia. The bones were carefully analyzed and described. The Tapirus animals emerged on Earth in the beginning of Pleistocene and in South America in the Miocene. The bones of T. terrestris are protuberant and resistant with accidents that, apparently help to cursorial displacement. As this is a cursorial animal, it has specific morphological adaptations that relates to its niche and habitat.